Improvement of a country home - Kahl, Clara Myrtle (My University, 1907)
Introduction: The work of landscape gardening or of beautifying the home grounds in the country is better to be planned and worked out in a natural way. The outward appearance must be considered, and, though many farms are not planned and one may think that a plan is not necessary if the natural conditions are to be retained around his home, yet a plan is as much a necessity here as it is in artificial work in gardening. We judge fairly well of the sanitary, intellectual, and moral status of a community or even of the inhabitants of one dwelling, by the outward conditions. Where the grounds and buildings are kept in good condition and cleanliness is easily seen to be one of the rules observed in that place, the result pleases the eyes of all passersby, even though the place may be small and unpretentious. It would seem that any one who has no love of nature, lacks at least one quality of a man. So much real enjoyment and true happiness may be derived from the work if one has the ability to plan and work out his own home grounds. This task of improving and beautifying one’s home is not altogether a selfish matter. The standard of cleanliness will influence people to be rivals in transforming the plots of ground to beautiful and useful advantage.
Citation: Kahl, Clara Myrtle. Improvement of a country home. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Country Home; Home Improvement; Landscaping; Home Maintenance; Theses